Pseudocalcinosis Tumorale (Teutschlander Disease) in Chronic Hemodialysis Patients - Taie, Omaima; Taie, Najlaa; Eddich, Yassine; Chtata, Hassan (Journal of Clinical Nephrology, 2024)
Pseudotumoral calcinosis (CPT) is a condition characterized by the deposition of calcium phosphate crystals in the periarticular tissues, forming large calcified masses. Although the pathophysiology of CPT is not fully understood, an increase in the calcium-phosphate product beyond the precipitation threshold and severe hyperparathyroidism appear to play a significant role. Treatment remains controversial, with surgical excision often recommended. We report a case of CPT in a 74-year-old diabetic patient undergoing chronic hemodialysis who experienced progressively worsening pain in the left hip for six months, along with mobility difficulties. A CT scan revealed a calcified mass on the posterior thigh, likely explaining the electric shock-like pain, as well as compression of the superficial femoral artery causing decubitus pain resembling critical limb ischemia. The biological assessment showed elevated calcium-phosphate levels and hyperparathyroidism. Surgical excision is not indicated due to the mass’s proximity to vascular and nerve structures. This case highlights the diagnostic and therapeutic challenges of CPT, emphasizing the need for iterative angioplasties, considering that this condition is rare in chronic hemodialysis patients with calcified periarticular masses.